Síntese e estudo físico-químico de 1,3-imidazóis 2,4,5-trissubstituídos derivados de benzocalcogenazóis - Heck, Elisiane Frantz (2016)
In the following work, an unprecedented series of 2,4,5-trisubstituted 1,3-imidazoles were synthesized from 1,2-diketones and aryl aldehydes, targeting the union of two classes of heterocyclic rings, the imidazoles and benzocalcogenazoles in order to explore their physical, chemical and biological properties. The 1,2-diketones were obtained from a terminal arylalkyne oxidation reaction, with yields ranging from 80-95% and 84-90%, respectively, for derivatives of benzothiazoles and benzoxazoles. For the synthesis of 2,4,5-trisubstituted imidazole, used the modified Radziszewski multicomponent reaction, they are reacted where the 1,2-diketones and aryl aldehydes with ammonium acetate in acetic acid as solvent, at presence of BF3.OEt2 catalysts to obtain the imidazoles derivatives of benzoxazoles and SnCl2.2H2O for derivatives of benzothiazoles. The yields obtained for the compounds ranged from 72-98% and 68-94%, respectively. From the physico-chemical study, it was observed that the compounds fluorescence and the same varies with the substituent present in its structure. Five compounds, 2,4,5-trisubstituted imidazoles derivatives of benzoxazoles were evaluated for antinociceptive activity, and noted that one of these had a similar result to the positive control, indomethacin.